Thymic Size in Preterm Neonates with RDS and its Relation to Survival: A Prospective Observational Study - Sanober Wasim; Neerul Pandita; Braham Prakash Kalra; Nowneet Kumar Bhat; Manju Saini (JCDR Research and Publications Pvt. Ltd., 2017)
Introduction: Thymic size in neonates is represented by the Cardiothymic-Thoracic ratio (CT/T) as measured on chest X-ray. Various pre and post natal factors have been shown to affect thymic size in neonates. Respiratory Distress Syndrome (RDS) is an important cause of mortality in preterm neonates and CT/T ratio in infants with RDS may actually be larger, owing to a decrease in serum cortisol levels in them. We therefore intend to find out the thymic size in infants diagnosed with RDS and whether it is related to survival. Aim: To determine the thymic size in preterm neonates with RDS and their relation to survival and to determine which antenatal and post natal factors have an influence on, or correlation with thymic size. Materials and Methods: The study was conducted in the NICU of Department of Pediatrics, Himalayan Institute of Medical Sciences, Dehradun, India, over a period of nine months. Premature (<37 weeks gestation) neonates admitted in NICU with clinical evidence of RDS, (Silvermann's score ≥3) and a chest X-ray suggestive of RDS were included in the study. CT:T ratio was determined on chest X-ray and compared between survivors and non-survivors. Results: Total 42 neonates were enrolled in the study. The mean±SD, CT:T in the study was 0.367±0.026. The CT:T in neonates who survived and those who expired was 0.36 and 0.38 respectively. A neonate with a CT:T of less than 0.403 had a 50% probability of survival. Although, CT:T was higher in the non-survivor group, the result was not statistically significant (p=0.33). Gestational age, sex, mode of delivery, administration of antenatal steroids or presence of birth asphyxia or sepsis did not affect the CT:T ratio. Conclusion: A large CT:T on X-ray chest can be used as a prognostic marker. Preterms with a CT:T of more than 0.40 have a poorer prognosis in terms of survival.